Dynamic of Distributed Parameter Systems; From Infinite to Finite Systems (The International Journal of Engineering & Information Technology (IJEIT), 2016)
This work focuses on describing the dynamicbehavior of distributed parameter systems by means ofspatial discretization. In control and system theory literature, distributed parameter systems are simply thesystems that are represented mathematically by partialdifferential equations. Thus, the key notion of this work isrepresenting the dynamic behavior of distributed parametersystems by means of spatial discretization of the dynamics ofthe system. Spatial discretization, or lumping, aims totransform a partial differential equation to a set of ordinarydifferential equations. The proposed concept approximatesthe dynamic behavior of the physical system by lumping itto small tranches and then using the finite differencesmethod to interconnect formally these lumps and simulatesthe dynamic of the overall system.